Super‐Corotating Flows in Plasma Disk Within 30 Jupiter Radii - Jian‐Zhao Wang; Fran Bagenal; Robert J. Wilson; Peter A. Delamere; Xin Cao; Edward Nerney; Robert W. Ebert; Philip W. Valek; Frederic Allegrini; Jamey R. Szalay (Geophysical Research Letters)
Abstract Plasma circulation and magnetic reconnection are crucial for understanding the dynamics of Jupiter's magnetosphere. Previous studies identified hundreds of reconnection sites at distances of 50–100 RJ from magnetic field signatures. Recent analysis of thermal plasma data from the Juno/JADE instrument shows super‐corotating flows exist in the pre‐dawn sector, suggesting that the internally driven reconnection could be occurring much closer to Jupiter. In this study, we present cases of super‐corotating flows exceeding 120% corotation observed at the nightside equator. In Case 1, a super‐corotating outflow event is observed at 26.9 RJ and is accompanied by flux rope plasmoids. In Case 2, a super‐corotating inflow event is observed at 24.7 RJ and is accompanied by plasma heating and density depletion, with a strong enhancement in Bθ indicating the presence of a dipolarization front. These observations provide evidence of super‐corotating flows accelerated by reconnection events.